ገበታ: የአየር ለውጥን መቋቋም ስለሚችሉ የተሻሻሉ የእንስሳት መኖ ቴክኖሎጂዎች የራዲዮ ፕሮግራም፡ ክፍል ሁለት - International Livestock Research Institute (International Livestock Research Institute, 2022)
In episode two, which aired on Debre Birhan Fana FM 94.0 on 1 July 2022, Kindu Mekonnen, senior scientist–Crop Livestock Systems at ILRI, gave an overview of the Africa RISING project in Ethiopia and explained some of the technologies it has introduced in feed and forage development. The radio program also presented a farmer's experience on the production and utilization of cultivated forage in North Shewa.